Nitrogen and phosphorus fertilization for groundnut in saline soil - A Taufiq; A Wijanarko; A Kristiono (Journal of Degraded and Mining Lands Management, 2018)
Groundnut cultivation on saline soil facing complex problems associated with high electrical conductivity (EC), toxic effects of Na cation, imbalance nutrients, and N and P deficiency. Objective of this research was to determine optimum rate of N and P fertilizers for groundnut on saline soil. The trial was conducted on saline soil in Lamongan (EC 8-15 dS/m, pH>8.0, low N, high P) and Tuban (EC 8-16 dS/m, pH>8.0, low N and P) during dry season year 2017. Treatment consisted of two factors, and the combinations were arranged in a completely randomized block design with three replications. The first factor was four N fertilizer rates (0, 23, 46, and 69 kg N/ha), and the second factor was four P fertilizer rates (0, 36, 72, and 108 kg P2O5/ha). Results showed that nitrogen fertilization had no effect on plant height, number of filled pod and plant stand, but improved chlorophyll content, increased100 seed weight, harvest index and yield. Phosphorus fertilization had no effect on all parameters observed, except on 100 seed weight and plant stand. The yield response to N fertilization was linear and quadratic, depending on the location. The optimum N rates was 62-69 kg N/ha. The results indicated that N fertilization had more important role than P fertilization for increasing groundnut yield on saline soil, although the growth did not improve